Diabetes Burnout Among the Elderly With Type 2 Diabetes - Ummu Muntamah; Dewi Siyamti; Medina Sianturi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
Diabetes mellitus (DM) is one of the most prevalent chronic diseases among the elderly, often leading to complications, dependency, and psychosocial burdens. Globally, over 20% of adults aged ≥65 years live with DM, and in Indonesia, its prevalence among the elderly reaches 19.2%. Despite this high burden, limited studies have addressed diabetes burnout (DB) in elderly patients, particularly within cultural contexts where family caregivers play a central role. This study aimed to explore the level of burnout in the elderly with DM and identify contributing factors. A descriptive-analytical quantitative design was applied involving 176 elderly DM patients registered in the Prolanis program at Semarang Regency Health Center, selected using purposive sampling. Data were collected using the Diabetes Burnout Syndrome (DBS) questionnaire and analyzed with descriptive statistics, chi-square test, and logistic regression. Findings showed that most participants were female, had a high school education, and had lived with DM for less than five years. Gender and education had a significant influence on DBS scores (p < 0.005). Burnout was higher among women, patients with DM >5 years, and those with a bachelor’s degree. Education emerged as the most influential factor, with higher education levels associated with an 11.76-fold increased risk of burnout (p < 0.001). Conclusion: Education plays a dominant role in shaping burnout among the elderly with DM. Interventions tailored to demographic characteristics, disease duration, and employment status, supported by social support and health education, are crucial for reducing burnout and enhancing chronic care.